2015
DOI: 10.1038/srep13091
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Decrement Drives Thermogenic Program In Adipose Cells

Abstract: Adipose tissue metabolically adapts to external stimuli. We demonstrate that the induction of the thermogenic program in white adipocytes, through cold exposure in mice or in vitro adrenergic stimulation, is accompanied by a decrease in the intracellular content of glutathione (GSH). Moreover, the treatment with a GSH depleting agent, buthionine sulfoximine (BSO), recapitulates the effect of cold exposure resulting in the induction of thermogenic program. In particular, BSO treatment leads to enhanced uncoupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 59 publications
3
31
0
Order By: Relevance
“…In summary, we attempted to extend current data on the obesity-resistance conferred by GSH depletion [13, 14] by characterizing the metabolomic profile of BSO-treated mice. Inhibition of GSH synthesis had widespread effects on the amino acid and fatty acid metabolomes, and on protein and fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we attempted to extend current data on the obesity-resistance conferred by GSH depletion [13, 14] by characterizing the metabolomic profile of BSO-treated mice. Inhibition of GSH synthesis had widespread effects on the amino acid and fatty acid metabolomes, and on protein and fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…These are mice in which glutamate cysteine ligase (GCL), the rate-limiting GSH synthesis enzyme, is inhibited by a genetic defect (GCL-modifier subunit knockout, Gclm -/- ) [11, 12] or by buthionine sulfoximine (BSO) [13, 14]. Gclm -/- mice also exhibit protection against fatty liver, and hepatic suppression of the lipogenic enzyme stearoyl CoA desaturase-1 (SCD1) [11, 12], but these features have not been tested in BSO-treated mice.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, brown adipose tissue (BAT) is involved in glucose clearance in the body thus suggesting that its dysfunction during stage of life could participate in age-related metabolic diseases. As consequence, BAT has currently gathered increasing attention as a therapeutic target for overwhelming human obesity and related metabolic disorders (Tseng et al, 2010 ; Lettieri Barbato et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The browning process was considered an adaptive mechanism to alleviate redox pressure. Furthermore, accumulating evidence have suggested that the induction of the molecular events that orchestrate adipocyte differentiation, metabolism, and even the efficiency of mitochondrial metabolism are driven by changes in the intracellular redox state, such as physiological NADPH oxidase‐induced reactive oxygen species (ROS) and glutathione (GSH) redox state . In addition, a previous study reported that adipocyte differentiation may be enhanced under conditions promoting intracellular and mitochondrial compartment oxidation .…”
Section: Discussionmentioning
confidence: 99%